KEBIJAKAN KRIMINAL DALAM MENANGGULANGI KENAKALAN REMAJA - Abdul Kholiq (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
outh are the future leaders of a nation. In addition to things that have been encouraging with the activities of teenagers lately such as increasingly actively participating in student organizations and increasing achievement, we also see the flow of moral decline that is increasingly prevalent among some of our young people, who are better known as delinquency. adolescents such as student fights, narcotics distribution, drug use, liquor, snatchers and so forth. Cases of juvenile delinquency can be influenced by several factors, namely family factors, school factors, community factors and economic factors, and therefore need to be addressed separately. The countermeasures are in the form of non-penalties that can be carried out individually and socially, preventively, by non-governmental organizations and also by the government, in addition to countermeasures also in the form of penalties, namely by giving sanctions.